Legal Aspects of Import Management of Palm Fiber and Coconut Fiber by an importing company in Indonesia - Bachry, Ramadhana Anindyajati; Surya, Andika; Muchajar, Muchajar; Daulay, Fikri Fathin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study intends to find out on how the mechanism in importing commodity such as coconut fiber and palm fiber. This is expected to provide an overview to readers, especially importers, not to mention the company that being the object of the authors research is the first company that imported this kind of commodity. This research was compiled and carried out with qualitative research methods. The data is collected through copies of documents, open information and information obtained from interviews, obrservation and notes that have been provided. The result of this study illustrate that the Perusahaan Pengimpor of the commodity that discussed must go through various procedures ranging from obtaining import permits, obligations in customs aspects, managing plant & quarantine permits, to tax obligations arising from importation activities carried out.